Using the alternative model of personality disorders for DSM-5 traits to identify personality types, and the relationship with disordered eating, depression, anxiety and stress - Tanya Gilmartin; Caroline Gurvich; Joanna F. Dipnall; Gemma Sharp (Journal of Eating Disorders)
Abstract Background There is a substantial and growing evidence base that has identified three distinct personality types (Overcontrol, Undercontrol and Resilient) among samples of individuals with eating disorders, as well as non-clinical samples. Even in studies where up to six personality types have been identified, the three core types representing Overcontrol, Undercontrol and Resilient consistently emerge. The aim of the research was to explore whether latent Overcontrol and Undercontrol personality types could be identified using pathological personality types as part of the Alternative Model for Personality Disorders published in DSM-5. We further aimed to understand how these personality types were associated with eating pathology, depressed mood and anxiety. Methods A total of 391 women, 167 men and 10 gender-diverse individuals aged 16 to 31 years completed measures of the alternative model of personality disorder traits, disordered eating behaviours, eating pathology, depression, anxiety and stress. A systematic four-step process using hierarchical, k-means, and random forest cluster analyses were used to identify the best fitting cluster solution in the data. Results The results revealed a four-cluster solution that represented overcontrol, undercontrol, resilient and an antisocial/psychoticism cluster. The overcontrol, undercontrol, and antisocial/psychoticism types were all associated with increased disordered eating, eating pathology, depression, anxiety and stress compared to the resilient types, with the undercontrol cluster scoring significantly higher than the other three clusters on all measures of clinical pathology. Conclusions Pathological personality traits, as conceptualised within the DSM-5 alternative model of personality disorders may have merit for identifying overcontrol and undercontrol personality types. Our findings provide additional evidence that both overcontrol and undercontrol personality types are associated with increased eating pathology, depression, anxiety and stress.